Analisis Hasil Belajar Siswa dalam Pembelajaran Problem Based Learning (PBL) Materi Kinematika Gerak Lurus - Azzahra, Maura; Jumini, Sri; Ariyanto, Agus; Hamzah, H (Universitas Sebelas Maret, 2023)
The aim of this research is to determine the improvement in physics learning outcomes in the kinematics of rectilinear motion material and student responses to the application of the Problem Based Learning (PBL) learning model in the learning process. This research is included in the type of Classroom Action Research (PTK). The subjects in this research were students of class XI Science 4 MA Negeri 1 Wonosobo for the 2023/2024 academic year with a total of 36 students. This research resulted that the overall percentage of individual completeness increased from cycle 1 to cycle II, namely from 55.6% to 78% and the overall percentage of classical completeness also increased, namely from 60% to 80%. Student responses tend to be positive where students state they are happy with the learning process using the Problem Based Learning (PBL) learning model. This research can be concluded that the application of the Problem Based Learning (PBL) learning model can improve the physics learning outcomes of class XI IPA 4 MA Negeri 1 Wonosobo students on the Kinematics of rectilinear motion material